The influence of social media marketing on consumer brand engagement and brand knowledge in fast food products - Zahra, Tsabita (Manajemen dan Bisnis, 2025)
In the digital era, social media has become a crucial platform for businesses to enhance brand knowledge and consumer-brand engagement, especially in the fast food industry. This study examines the impact of social media marketing on these variables, focusing on factors like interaction, entertainment, customization, electronic word-of-mouth (EWOM), and trendiness. The research method employs a quantitative descriptive approach with a sample size of 116 respondents. Data was collected through online questionnaires distributed to active social media users and analyzed using SmartPLS software. The findings reveal that while interaction, EWOM, and trendiness positively influence consumer-brand engagement and subsequently improve brand awareness and brand image, entertainment and customization do not significantly affect engagement. The study suggests that fast food companies should prioritize active consumer interaction on social media, stay updated with trends, and create engaging content to strengthen brand connections and image. Future research should consider a mixed- method approach and explore strategies to enhance response rates and engagement in surveys.